The effects of Jesus and God on pro-sociality and discrimination - Lane, Tom (2020)
This study contributes to the debate over whether religion is a force for social good or harm. It shows that different belief concepts within the same religion can have different effects on distributive behaviour. A dictator game experiment, with two different charities as potential recipients, measures how priming the concepts of God and Jesus affects both the pro-sociality of Christians and their propensity to discriminate against LGBTQ people, an identity group traditionally opposed by their religion. Priming Jesus significantly raises the amounts Christians give to charity, but priming God has no such effect. Christians are found, at borderline significance, to discriminate against LGBTQ people, but this discrimination does not significantly increase when Jesus or God are primed.